Uganda's Economic Reforms : insider accounts - Kuteesa, Florence; Tumusiime-Mutebile, Emmanuel; Whiteworth, Alan; Williamson, Tim (Oxford University Press, 2010)
In recent years Uganda has consistently been one of the fastest growing economies in Africa, leading to a substantial reduction in poverty. This book looks at how the country managed to carry out this economic transformation in the wake of Idi Amin's rule and the civil war of the 1980s.